Linking subjective financial well-being and compulsive buying behavior among college students: How Islamic financial literacy makes different - Subur Karyatun (LPMP Imperium, 2023)
This study aims to enhance our understanding of the reciprocal association between subjective financial well-being and compulsive buying behavior while also considering the role of Islamic financial literacy as a boundary condition. The data for this research were collected in two phases from a sample of 266 students in Jakarta. The collected data were then analyzed using macro process version 4 to assess the proposed hypotheses. The study's findings confirm that subjective financial well-being and Islamic financial literacy negatively impact compulsive buying behavior. Moreover, the study reveals a subsequent influence of compulsive buying on future financial well-being, supporting a reciprocal relationship. Additionally, Islamic financial literacy plays a crucial role in mitigating the effect of financial well-being on compulsive buying behavior. Public interest statements Technological developments have brought changes in consumer behavior and sometimes have a negative impact on compulsive buying behavior. This research helps mitigate the effects of subjective financial well-being on compulsive behavior and how the two influence each other. In addition, students need to be given an understanding of Islamic financial literacy to control their buying behavior. Article history Received: 6/12/2023 | Revised: 7/4/2023 | Accepted: 7/4/2023 | Online First: 7/5/2023